Financing Risk Mitigation Strategy with Governance Approach, Local Wisdom, and Religiosity at Sharia Rural Bank (BPRS) of Riau - Putra, P. Adiyes; Sapparudin, Sapparudin; Anggraeni, Tuti; Nurnasrina, Nurnasrina (Ekonomi Syariah IAIN Kudus, 2024)
This study presents an innovative approach to financing risk mitigation strategies at BPRS in Riau by identifying causal factors, solutions, and strategies. Using a qualitative approach with the Analytic Network Process (ANP) method involving regulators, practitioners, and academics to reveal the interconnection between internal and external factors, sociocultural dimensions, and religiosity affecting financing performance. The findings show that implementing good governance, community and local wisdom, and religious values in the customer selection process reduces financing risks and strengthens the relationship between Sharia Rural Bank (BPRS) and the community. The results of this study provide significant contributions to developing a more comprehensive and sustainable risk mitigation framework, policies, and practices for BPRS in Riau, inspire the application of similar principles in other Islamic financial institutions, and encourage regulators to develop regulations to support the development of BPRS.